Implementation of tahsin learning in enhancing students’ memorization ability at I’dadul Mu’allimin Tahfizhul Qur’an Shighor Isy Karima Karanganyar - Munawar Kholil; Mujiburrohman (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study is motivated by the importance of tahsin (Qur’anic recitation improvement) as the foundation of Qur’an memorization (tahfizh). Correct recitation according to the rules of tajwid not only preserves the authenticity of the Qur’anic text but also significantly influences the quality of students’ memorization. IMTAQ Shighor Isy Karima Karanganyar, an institution of I’dadul Mu’allimin Tahfizhul Qur’an, applies an integrated tahsin program within its tahfizh curriculum, making it a relevant object of study. The objectives of this research are to describe the forms of tahsin learning, analyze its implementation in strengthening memorization, and identify supporting and inhibiting factors. This research employed a descriptive qualitative method using observation, interviews, and documentation. Primary data were obtained from the principal, tahfizh curriculum manager, and supervising teachers, while secondary data came from institutional documents and archives. The findings show that tahsin learning at IMTAQ is conducted through three stages: planning, implementation, and evaluation. Its implementation effectively enhances students’ memorization through recitation matriculation, talaqqi, repetitive practice, and strict evaluation. Supporting factors include competent teachers, curriculum and institutional support, and a religious environment, while inhibiting factors involve differences in students’ basic abilities, limited time, and technical constraints. The implication of this study is that other Qur’an memorization institutions should integrate tahsin into their curricula to produce hafidz who not only memorize extensively but also recite fluently and accurately.